Experimental study on the influence of model variations on the airway occlusion of an obstructive sleep apnea patient. (23rd June 2021) - Arnold, M.; Burgmann, S.; Bonitz, L.; Pugachev, A.; Janoske, U.
Abstract: This study deals with the analysis of model parameters to mimic the airway collapse of an obstructive sleep apnea patient during nasal breathing. Different material properties and geometry variations of a patient-specific airway model are analyzed in detail. The patient-specific airway geometry is obtained from MRI data. A completely rigid model is compared to two partly elastic variations with different elasticities. Furthermore, the influence of the nasal cavities and the treatment effect of a mandibular protrusion are studied. Rigid model parts are 3D-printed and elastic parts cast from silicone. The models are analyzed under the impact of a transient airflow which is realized through a computer controlled piston pump. The results suggest, that, for moderate deformations, the elasticity of the soft tissue replicate influences rather the level of the pressure drop inside the airway than the shape of the pressure curve. The same suggestion can be made for the influence of the nasal cavities. Often, the spatial location of the minimum pressure is taken as the collapse site of the airway geometry. This study demonstrates, that the spatial locations of the minimum pressure and the maximum deformation do not match. This reveals the importance of a coupled approach of soft tissue and airflow analysis in the search of the collapse site and therefore the best treatment option. A treatment effect of the mandibular protrusion can be anticipated with an accurate patient-specific airway model.